Sports engineering : comparison of blade designs in traditional paddle sports - Mohd Faizal Selamat. (2009)
The objective of conducting this study is to analyze the effect of blade geometry on the rowing efficiency for paddles used in both traditional and popular paddling sports. This was achieved through a deep understanding of how a paddle works and applying the concepts of fluid dynamics, particularly in the fields of drag and pressure. The author selected a Macon paddle, which incorporates a design derived by technological means, and compared it against the dragon boat and Royal Thai Barge paddles, which represented the traditional boating equipment. A rectangular paddle blade was added to further enhance the study.